2007
DOI: 10.1063/1.2679902
|View full text |Cite
|
Sign up to set email alerts
|

Injection charge assisted polarization reversal in ferroelectric thin films

Abstract: The authors have investigated the polarization reversal on ferroelectric thin films caused by a grounded tip on 50-nm-thick Pb͑Zr, Ti͒O 3 films. Backswitching occurred when the grounded tip recontacted a "freshly" switched area. It is believed that the upper part of the film switches back due to the field between the grounded tip and previously injected charges. During dynamic operation, partial backswitching was observed during pulsed writing using pulse widths of 1 ms. The results show that polarization reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…Several subsequent scans of the same region revealed that the mechanically written domains were robust even when imaged with a grounded tip under normal loading force, excluding the possibility of the grounded tip causing the reorganization of the domain structure. [30] These results suggest a domain rearrangement mechanism, involving interplay between ferroelectric and ferroelastic switching, which could be induced by either electric field, localized stress or a combination of the two stimuli. [31] In order to systematically probe and isolate the role of applied stress during switching, an adaptation of the switching spectroscopy piezoresponse force microscopy (SS-PFM) technique with direct control over the applied tip force was used.…”
Section: Resultsmentioning
confidence: 99%
“…Several subsequent scans of the same region revealed that the mechanically written domains were robust even when imaged with a grounded tip under normal loading force, excluding the possibility of the grounded tip causing the reorganization of the domain structure. [30] These results suggest a domain rearrangement mechanism, involving interplay between ferroelectric and ferroelastic switching, which could be induced by either electric field, localized stress or a combination of the two stimuli. [31] In order to systematically probe and isolate the role of applied stress during switching, an adaptation of the switching spectroscopy piezoresponse force microscopy (SS-PFM) technique with direct control over the applied tip force was used.…”
Section: Resultsmentioning
confidence: 99%
“…For polarization, the underpinning phenomena are similar, except that regions with switched polarization play the role of a virtual electrode. The accumulation, injection, and transport of ionic charge now becomes an inherent part of the switching process, as illustrated by phenomena such as the formation of bubble domains during back switching, 80,242 domain shape stability loss, 85 and chaos 86 during ferroelectric switching.…”
Section: A Surface Ionic Screeningmentioning
confidence: 99%
“…Since then, this chemical screening behavior was explored in depth in a beautiful set of experimental and theoretical work by a group at Argonne, 78,79 and further evidence of surface screening behavior was gained via observations of e.g. back switching [80][81][82][83][84] and chaotic screening of ferroelectrics by PFM. 85,86 However, these studies demonstrated that KPFM (or any other long-range field contrast) is controlled by the interplay between polarization and (poorly understood and controlled) screening and charging processes, and does not provide information on ferroelectric behavior per se.…”
Section: Iia Basic Pfmmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Abnormal switching behaviors, including backswitching, 12,15,[21][22][23] polarization reversal by the "wrong" polarity of the switching voltage 7,11,17,19 and switching along the path of the unbiased SPM tip 18, 24 were reported. These phenomena were attributed to the charge injection 12,15 , screening of the applied electric fields 25 and ferroelastoelectric switching.…”
mentioning
confidence: 99%
“…In the case of switching against applied electric field, 12,15,19 electric field induces in the tip are due to the injection of the screening charges near the tip. In the case of backswitching with formation of the ring-shaped domains, 18,[21][22][23] this is due to charges on the charged domain walls of the non-through domain. The results of the analytical and numerical calculations demonstrate existence of the switching conditions under grounded SPM tip.…”
mentioning
confidence: 99%